THE ANALYSIS OF LESSON PLANS DESIGNED BY THE ENGLISH TEACHER OF JUNIOR HIGH SCHOOL AT SMPN 26 MAKASSAR - Mu’jizat Fitrani; Muh. Arfin Muh. Salim; Firman (FKIP Unismuh Makassar, 2021)
This study aims to (1) describe the preparation of the lesson plans for English teachers at SMP Negeri 26 Makassar (2) to describe the constraints for English teachers at SMP Negeri 26 Makassar in preparing the lesson plans and their efforts, and (3) describe the suitability of the components of the lesson plans for English teachers in SMP Negeri 26 Makassar. This research is a qualitative descriptive study. The subject of this study was an English teacher at SMP 26 Makassar consisting of 3 English teachers. The object of this research is the learning implementation plan that has been made by the teacher. Data obtained through interviews and documentation. The data obtained were then analyzed using qualitative data analysis techniques. The results of the data analysis were then concluded according to the research problem.